DETERMINATION OF HEAVY METALS CONCENTRATION IN RAW MILK OF AWASSI SHEEP GRAZED IN THE POLLUTED AREA BY OIL REFINERY EFFLUENTS IN KWASHE INDUSTRIAL AREA - Meshabaz, Ronak A.; Umer , Mustafa I. (Science Journal of University of Zakho, 2023)
Nowadays, heavy metals are regarded as the most significant contaminants due to industrial activities and have an impact on their presence in milk. The presence of heavy metals in milk could have a serious negative impact on public health. The current study aims to determine the amount of various heavy metals (Pb, Cu, Co, Cd, Cr, Ni, Fe, and Zn) in raw Awassi ewe’s milk collected from Kwashe industrial area, Duhok province, Kurdistan Region, Iraq. The sheep were grazed in Sulaivany plain contaminated by drains of industrial effluents of several crude oil refineries and other 200 different factories. Atomic absorption spectrophotometer was utilized to analyze the milk specimens after wet digestion. Results displayed that the heavy metals concentration was in the range of 3.64-4.27 mg/L for Pb, 0.59-1.13 mg/L for Cu, 0.01-0.09 mg/L for Co, 0.12-1.46 mg/L for Cd, 0.24-0.29mg/L for Cr, 0.89-0.99 mg/L for Ni, 0.89-0.94 mg/L for Fe and 3.99-6.13 mg/L for Zn. Statistical analyses showed that excusing Cr, and all other studied heavy metals concentrations were higher than the human-health safety recommended.  Furthermore, among the heavy metals in the current study, the Zn was the highest mean value recorded (4.99 mg/L) and it exceeded the limited value (3.8 mg/L) by WHO/FAO, (1999). The permissible level of pb in milk is 0.05 mg/L, and the mean concentration of pb in the milk sample (3.99 mg/L) was significantly higher than the permissible value. Moreover, the mean value of Cd (0.75 mg/L), Cu (0.79 mg/L), Co (0.038 mg/L), Ni (0.948 mg/L), and Fe (0.91 mg/L) were above the limited value (0.01 mg/L) for Cd, 0.03 mg/l for Cu, (0.001-0.008) for Co, (0.1mg/L) for Ni and 0.1 for Fe, respectively. While the Cr concentration (0.27 mg/L) was lower than the recommended level (0.3 mg/L). Therefore, it was observed that the amount of heavy metals in the sheep milk utilized in this investigation possesses a health risk. Hence, it is always needful to persuade the pollutants in milk in the current area.
Keywords: Heavy metals; Milk; polluted area; oil refinery; Sheep; Kwashe industrial area